Isolation and analytical characterization of local Malaysian Leech Saliva extracts - Alaama, Mohammed; Alnajjar, Manar; M. Abdualkader, Abdualrahman; Mohammad, Abbas; Merzouk, Ahmed (IIUM Press, 2011)
Leech saliva contains biologically active compounds that are mainly proteins and peptides. In this study a modified and smooth extraction method of saliva was used without leeches’ scarification. UV and Bradford Assay protein methods showed that the saliva extract contains high concentrations of proteins. RP-HPLC chromatogram revealed that more than 30 different peaks were observed in leech saliva extract. Gel electrophoresis revealed the existence of proteins and peptides with different molecular weights. The gel showed up to 25 different bands. Comparison of gel electrophoresis data with protein database revealed the closeness of four molecular weights to known proteins from Hirudinaria leech family. Other proteins detected by gel electrophoresis may be related to completely new biologically active proteins and peptides in the saliva extract or to a modification (isoforms) of the existing ones or finally to a mixture of both